Changes in emotional processing following interoceptive network stimulation with rTMS. (15th May 2019) - Mai, Sandra; Braun, Julia; Probst, Viktoria; Kammer, Thomas; Pollatos, Olga
Abstract: Theories of emotion suggest a close relation of interoception and emotion. However, knowledge of underlying neuronal networks is still sparse. Repetitive transcranial magnetic stimulation (rTMS) is one neurostimulation method allowing causal conclusions between functions and brain regions via stimulation or inhibition of underlying brain structures. In this study, rTMS with a continuous theta burst stimulation (cTBS) protocol was used aiming for inhibition of important interoceptive network structures (frontotemporal insular network and right somatosensory cortices). Stimulation effects were investigated on interoceptive accuracy (IAc), emotional evaluation and neuronal correlates of emotional picture processing in 18 male participants. The main findings were an emotional flattening in subjective valences for affective stimuli after inhibition of the frontotemporal anterior insular network and of somatosensory cortices, being mirrored in visual evoked potentials as increased N2/decreased P3, indicating an initial orientation reaction followed by decreased attentional processing of positive stimuli. Moreover, cardiac and respiratory IAc were positively associated with P3 amplitudes and negatively related to positive valence ratings. Positive associations of decreases of cardiac/respiratory IAc with decreases of arousal ratings and decreases of P3 amplitudes for negative stimuli after inhibition of the frontotemporal insular network and after inhibition of somatosensory cortices allow the conclusion of a causal relationship between reduced activity in interoceptive network structures and blunted emotional processing of visual stimuli. Our results suggest that both arousal, and valence aspects of emotional processing are disturbed after inhibition of interoceptive network structures, confirming core assumptions of peripheral theories of emotions and models of interoceptive predictive coding. Highlights: The interoceptive network was inhibited with continuous theta burst stimulation (cTBS) during emotional processing. Disturbance of emotion processing after cTBS of the frontotemporal anterior insula network/somatosensory cortices. N2/P3 mirrored disturbance of emotion processing. Conclusion of causal relation between reduced activity in interoceptive network and blunted emotional processing. Confirmation of core assumptions of peripheral theories of emotions and of models of interoceptive predictive coding.